Bending the Curve in Cardiovascular Disease Mortality: Bethesda + 40 and Beyond. Issue 8 (23rd February 2021) - Goff, David Calvin; Khan, Sadiya Sana; Lloyd-Jones, Donald; Arnett, Donna K.; Carnethon, Mercedes R.; Labarthe, Darwin R.; Loop, Matthew Shane; Luepker, Russell V.; McConnell, Michael V.; Mensah, George A.; Mujahid, Mahasin S.; O'Flaherty, Martin Enrique; et al.
Abstract : More than 40 years after the 1978 Bethesda Conference on the Declining Mortality from Coronary Heart Disease provided the scientific community with a blueprint for systematic analysis to understand declining rates of coronary heart disease, there are indications the decline has ended or even reversed despite advances in our knowledge about the condition and treatment. Recent data show a more complex situation, with mortality rates for overall cardiovascular disease, including coronary heart disease and stroke, decelerating, whereas those for heart failure are increasing. To mark the 40th anniversary of the Bethesda Conference, the National Heart, Lung, and Blood Institute and the American Heart Association cosponsored the "Bending the Curve in Cardiovascular Disease Mortality: Bethesda + 40" symposium. The objective was to examine the immediate and long-term outcomes of the 1978 conference and understand the current environment. Symposium themes included trends and future projections in cardiovascular disease (in the United States and internationally), the evolving obesity and diabetes epidemics, and harnessing emerging and innovative opportunities to preserve and promote cardiovascular health and prevent cardiovascular disease. In addition, participant-led discussion explored the challenges and barriers in promoting cardiovascular health across the lifespan and established a potential framework for observational research and interventions that would begin in early childhood (or ideally in utero). This report summarizes the relevant research, policy, and practice opportunities discussed at the symposium. Abstract : Supplemental Digital Content is available in the text.